1999
DOI: 10.1212/wnl.52.5.932
|View full text |Cite
|
Sign up to set email alerts
|

Striatal dopaminergic function in restless legs syndrome

Abstract: These PET findings support the hypothesis of central dopaminergic dysfunction in RLS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
205
3
12

Year Published

2000
2000
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 396 publications
(231 citation statements)
references
References 33 publications
11
205
3
12
Order By: Relevance
“…18 F-or 11 C-labeled L-dopa is an analog of L-dopa, and this positron-emitting compound is used clinically to trace the dopaminergic pathway and to evaluate presynaptic function. Uptake of L-dopa labeled with a positron-emitting radionuclide refl ects the synthesis rate of DA in the terminals, under the conditions of PET [32,33] . Studies with PET and radionuclidelabeled L-dopa and their main fi ndings are summarized in [34,35] .…”
Section: Pet Studies Of Presynaptic Da Synthesismentioning
confidence: 99%
“…18 F-or 11 C-labeled L-dopa is an analog of L-dopa, and this positron-emitting compound is used clinically to trace the dopaminergic pathway and to evaluate presynaptic function. Uptake of L-dopa labeled with a positron-emitting radionuclide refl ects the synthesis rate of DA in the terminals, under the conditions of PET [32,33] . Studies with PET and radionuclidelabeled L-dopa and their main fi ndings are summarized in [34,35] .…”
Section: Pet Studies Of Presynaptic Da Synthesismentioning
confidence: 99%
“…Finally, the co-occurrence of these syndromes in this family suggests that there might be a pathophysiological relationship between RLS, chronic motor tic disorder and MA. Some similar clinical characteristics of RLS and motor tic disorder, in particular the urge to move which precedes it and the subsequent alleviation by motor activity, indicate an implication of the basal ganglia and the limbic network in the pathophysiology of the two disorders [7,8]. Moreover, Barbanti et al [9] concluded that the high prevalence of migraine in TS might be linked to a dysfunction of the extrapyramidal system.…”
Section: Sirsmentioning
confidence: 98%
“…Striatal uptake of the [ 18 F] dopa or [ 11 C] L-dopa reflects the synthesis rate of DA in the terminals (Turjanski et al, 1999;Heinz et al, 2005). It has been showed that a decrease in dopaminergic presynaptic activity during abstinence or withdrawal is related to relapse in cocaine-dependent subjects (Dackis and Gold, 1985;Markou and Koob, 1991).…”
Section: Assessment Of Presynaptic Da Synthesis and Dat Of The Dopamimentioning
confidence: 99%